(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Biomass energy is an important component in the overall structure of renewable energy and has the greatest potential for increasing volumes. However, the peculiarities of the properties of agro-industrial residues are a significant disadvantage of their widespread use. The process of torrefaction allows to bring the characteristics of biofuel as close as possible to thermal coal. Different degree of heat treatment of biomass leads to a product with different heating value. Therefore, it is important to know the optimal mode of torrefaction, which will provide the best energy parameters of biofuels.Researches of torrefaction were carried out on the basis of educational and scientific laboratory "DAK GPS" of the State Agrarian and Engineering University in Podilia. The kinetics of the relative mass of different types of biomass at different processing temperatures was considered. The dependence of the degree of torrefaction on the heat treatment temperature is revealed. As shown by studies for most biomaterials of plant origin, we can distinguish the beginning of intensive transformation and its end, after which there is a sharp slowdown in weight loss, and, accordingly, and the energy density of the samples.